The Right of Prisoner in Correctional Institutions Cohabitation as a model - Al-Bustany, Tavga Abbas Towfiq; Saeed, Mohammad Sabah (Journal of Legal and Political Studies, 2020)
The problem that this research sheds light on is the extent to which the right to marital cohabitation of the inmate and the eviction of his wife throughout the period of its implementation of the punishment within the penal institutions are necessary, and whether or not its approval violates the purposes and purposes of the punishment or not? and the role played by caring for the physical and psychological health of the inmate in his preparation and qualification, especially since this problem has become one of the topics that did not approach positive jurisprudence, except in the near time and with great caution and did not unite with punitive systems.
Keywords: marital cohabitation; punishment; physical and psychological health; positive jurisprudence; caution